PARENTING STYLES IN ANAMBRA STATE: A CATALYST FOR STUDENT READING ATTITUDE DEVELOPMENT - Okonkwo, Nkechi Olivia (Current Journal of Library and Information Sciences (CJLIS), 2023)
Reading holds a pivotal role in human life, shaping individual vision, personality, and fostering connections with others. It empowers individuals, shielding them from ignorance and misinformation. This paper underscores the profound significance of cultivating a strong reading culture. Drawing from the insights of Ifedili (2009), it is evident that reading not only contributes to personal welfare and social progress but also nurtures international understanding, imparts essential skills, knowledge, and a positive attitude. Furthermore, reading liberates individuals from boredom and idleness, thus enriching both academic and real-life experiences. It transcends the boundaries of educational institutions and significantly enhances one’s prospects for success in education and life beyond the classroom. The undeniable connection between reading proficiency and scholastic achievement is highlighted, where competence in reading is not just advantageous but an imperative for overall success in education. Poor reading skills, if not addressed, lead to a path of frustration and academic failure. As emphasized by Oyeyemi (2005), reading acts as a conduit for acquiring knowledge from more informed minds, shaping thoughts and behaviors in accordance with the reader’s objectives. This process results in the development of modified thoughts, behaviors, attitudes, and contributes to personal and societal growth. This paper explores the profound impact of reading on personal and social development, emphasizing its role in building a well-rounded, informed, and successful individual.